Evaluation Of The Transformed Layer Of DLC Coatings After Sliding In Oil Using Spectroscopic Reflectometry - Ohara, Kenji; Masripan, Nor Azmmi; Umehara, Noritsugu; Kousaka, Hiroyuki; Tokoroyama, Takayuki; Inami, Shigeru; Zushi, Koji; Fujita, Masahito (Science Direct, 2013)
Diamond-like carbon (DLC) coatings continue to attract attention for their low friction and high wear resistance. The transferred or transformed layer, which has a high sp2 carbon content induced by cyclic friction, results in an ultralow friction coefficient in ambient air. However, there are few reports on such layers, especially the transformed layer in oil lubrication, because this transformed layer could be too thin to be measured quantitatively. M. Kano and C. Matta reported the 3 nm thickness of a sp2 carbon layer using EFTEM study. The spectroscopic reflectometry technique has been applied to measure the thickness of the transformed layer of the DLC's wear scar after friction under oil boundary lubrication. The purpose of this study was to develop a quantitative method for measuring the thickness of the transformed layer in hydrogen-free DLC (ta-DLC) and two types of hydrogenated DLC coatings. Then, we clarified the friction model of these DLC coatings under oil lubrication as the transformed layer was the solid lubricant film. Consequently, we observed that there were optimum ranges of wavelengths and optical models for measuring the transformed layer of the DLC. The optimum wavelength range was 300–500 nm, and the bi-layer model was the best for DLC1, which was the hydrogen-free DLC. For the thicker and un-transmissive coatings, which were hydrogenated DLC coatings, the ranges of wavelengths were 600–800 nm, and the optical model was hypothesized to be a single-layer model. From these optical models, we observed that the thicknesses of the transformed layers of the DLC coatings under oil boundary lubrication were approximately 10–200 nm in the hydrogen-free DLC and 0–200 nm in the hydrogenated DLC. From the analysis of the thickness of the transformed layer and surface roughness, σ⁎, of various DLC coatings, we observed that the friction coefficient of the DLC under oil boundary lubrication was determined by the possibility of breaking the transformed layer. This result strongly suggested that the DLC film was a material that realized self-surface modification. We believe that the results of this study could be developed as a guideline for designs of surfaces with DLC coatings.